Green Strategies and Business Growth in SMEs: Does Industry Type Matter? - Flora Samosir; Daniella Cynthia Sampepajung; Johannes Baptista Halik (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
This study investigates the influence of Eco Design Strategy (EDS) and Green Value Creation (GVC) on Business Growth (BG) among Indonesian Small and Medium Enterprises (SMEs), while examining the moderating role of Industry Type (IT). Utilizing a quantitative approach, data were collected from 195 SMEs across Jakarta, Surabaya, Bandung, and Makassar and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that both EDS and GVC significantly and positively impact business growth, highlighting the strategic importance of adopting sustainability practices. However, the moderating effect of industry type on the relationship between green strategies and business growth was found to be statistically insignificant. These findings provide empirical support for the integration of eco-innovation and green value generation as key drivers of competitive advantage, regardless of industry category. The study offers both theoretical implications for sustainability literature and practical insights for MSME managers seeking to enhance performance through environmental initiatives.